Lessons learnt through gender-based travel data collection and related sexual harassment in Sub-Saharan Africa. Issue 1 (2023) - Vanderschuren, Marianne; Allen, Heather; Krause, Philip; Lane-Visser, Tanya
Abstract: Background and objective: Key motivations for the study described in this paper were to gain insights into the differences in travel behaviour between males and females, as well as gender-based sexual harassment exposure in public transport in sub-Saharan Africa. The mobility and sexual harassment results, based on data collection in two African cities (Blantyre in Malawi and Lagos in Nigeria), is presented in this paper, to document the true extent of sexual harassment and ways in which sexual harassment practices affected women's mobility on the continent. The analysis aims to illuminate gender-based mobility differences and sexual harassment experiences, as well as provide some guiding principles towards addressing sexual harassment challenges. Method: and Data : This study developed a standardised gender-based travel and sexual harassment perception questionnaire that was applied via pen-and-paper, as well as technology (offline tablets) in the cities of Lagos (Nigeria) and Blantyre (Malawi). Overall, 1478 respondents participated. Approximately 58% of the sample in both cities were women. The data collected was analysed to highlight differences between male and female travel behaviour and differences in relation to exposure to sexual harassment whilst in the transport system. Results: Data revealed that women make more, shorter trips, while they carry a significantly higher sexual harassment burden. All parts of public transport trips are affected, including travelling to/from the system, while waiting for the vehicle and in the vehicle. The need for transfers increases the risk of crime and sexual harassment. This paper concludes that there is a need for improved policy frameworks, educational campaigns, for men and women, as well as the creation of safe reporting structures when sexual harassment does occur. Actions are needed in the two case study cities and beyond. Highlights: Gender-based legal and policy frameworks are scarce on the African continent. Data confirms that women and men experience sexual harassment differently and unequally. Travel-related sexual harassment will require action on many levels. Educational campaigns for women and men can drive behaviour and culture change. Low harassment reporting rates should be addressed by easily accessible, friendly and trustworthy grievance staff.